Audio Visual Snakes and Ladders Game Development for SPLDV - Rifatus Sholikah; Marhan Taufik; Adi Slamet Kusumawardana (Mathematics Education Journal, 2023)
Many students still need help understanding SPLDV material. This research aims to develop learning media for snakes and ladders assisted by audio-visual aids using valid and effective PPT to improve learning outcomes and student learning enthusiasm in learning the Two-Variable Linear Equation System. The study subjects were 18 grade VIII students at SMP Muhammadiyah 2 Malang. The research method used is development or Research and Development (R&D). Data collection techniques used are test questions and questionnaires. Data analysis techniques using data analysis, namely quantitative descriptive with and calculating the average value of the pretest and posttest and the average percentage of the questionnaire value and the categorization of the percentage results. The results of this study indicate that the average effect of media validation is 94% in the very good category. Student learning outcomes are seen from the average student scores before and after using the media, namely, 32.5 and 83.89, which states that there are differences in learning outcomes students before and after using the media, as well as from the response questionnaire data students' enthusiasm for learning obtained an average of 83.74% which means very good. This states that audio-visual assisted snake and ladder learning media using PPT in learning the Linear Equation System of Two Variables is valid and effective in improving learning outcomes and student learning enthusiasm in the learning process.